Pembentukan Karakter Religius Siswa Melalui Pembiasaan Keagamaan di SD Islam Tirtayasa - Mirna Mirna; Istinganatul Ngulwiyah; Zerri Rahman Hakim (Pusat Riset dan Inovasi Nasional, 2025)
Religious character is the main character that must be instilled in students as early as possible with the aim of forming a good personality and being able to apply it in everyday life. This study aims to analyze the existence of religious character in religious habits in schools, to determine the strategy of religious habits in forming religious character and to determine the success in forming students' religious character. The method used is a descriptive qualitative method with data collection techniques through interviews, observations and documentation. This research was conducted at SD Islam Tirtayasa as a place for research on data collection, findings and results. The results of this study indicate that after religious habits were carried out at SD Islam Tirtayasa, most students had characters that were in accordance with religious indicators, namely being obedient to Allah, disciplined, responsible, honest and respecting others.